Vodnik skozi anatomsko terminologijo, Ductio per terminologiam anatomicam / Vodnič kroz anatomsku terminologiju, Ductio per terminologiam anatomicam - Pejković, Božena; Jesenšek, Marko (University of Maribor Press, 2026)
A Guide to Anatomical Terminology. Ductio per terminologiam anatomicam. Illustrated quadrilingual (Slovenian, Serbian, Latin and Greek) vocabulary of anatomic terms with ethymological explanation of anatomic terms that are included in the international anatomic terminology is aimed to make anatomy more comprehensive and interesting for learning.